Impact of Factors on Indonesian Consumer Purchase Intentions for Counterfeit Luxury Goods: The Role of Social Media Influencers - Dahlia, Putri (Heca Sentra Analitika, 2023)
The surge in the consumption of luxury goods has led to an increase in the availability of counterfeit luxury items in the market. This proliferation of fake luxury products has inflicted financial and reputational damage upon luxury brands, undermining the carefully cultivated brand image over the years. The primary objectives of this study are to gain a deeper understanding of the factors influencing the purchase intentions of Indonesian customers towards counterfeit luxury products and to investigate the role played by social media influencers in this context. The study collected data through an online survey platform, obtaining 134 samples, and employed a multiple regression method for analysis. The research revealed that factors such as value consciousness, motivation, and social risk perception do not exert a positive influence on the purchase intentions of Indonesian consumers regarding counterfeit luxury products. Contrary to previous findings, these three hypotheses failed to support the current study's results, while two hypotheses were substantiated. The findings indicated that attitude and the impact of social media influencers have a significant and positive effect on the intention to purchase fake luxury products in Indonesia. In essence, the study concluded that a more favorable attitude towards counterfeit products increases the likelihood of purchase intentions, and the promotion of counterfeit luxury items by online influencers further stimulates consumer intentions to acquire non-authentic luxury goods.